Interacción de plagas con niveles de fertilización en la asociación maíz-caupí (Zea mays L. - Vigna unguiculata (L.) Walp.) - Martínez Tambito, E.A. (1982)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1982